Assessment of Surgical and Trauma Capacity in Potosí, Bolivia - Kevin J. Blair; Marissa A. Boeck; José Luis Gallardo Barrientos; José Luis Hidalgo López; Irene B. Helenowski; Benedict C. Nwomeh; Michael B. Shapiro; Mamta Swaroop (Ubiquity Press, 2017)
Background: Scaling up surgical and trauma care in low- and middle-income countries could prevent nearly 2 million annual deaths. Various survey instruments exist to measure surgical and trauma capacity, including Personnel, Infrastructure, Procedures, Equipment, and Supplies (PIPES) and International Assessment of Capacity for Trauma (INTACT). Objective: We sought to evaluate surgical and trauma capacity in the Bolivian department of Potosí using a combined PIPES and INTACT tool, with additional questions to further inform intervention targets. Methods: In June and July 2014 a combined PIPES and INTACT survey was administered to 20 government facilities in Potosí with a minimum of 1 operating room: 2 third-level, 10 second-level, and 8 first-level facilities. A surgeon, head physician, director, or obstetrician-gynecologist completed the survey. Additional personnel responded to 4 short-answer questions. Survey items were divided into subsections, and PIPES and INTACT indices calculated. Medians were compared via Wilcoxon rank sum and Kruskal-Wallis tests. Findings: Six of 20 facilities were located in the capital city and designated urban. Urban establishments had higher median PIPES (8.5 vs 6.7, 'P' = .11) and INTACT (8.5 vs 6.9, 'P' = .16) indices compared with rural. More than half of surgeons and anesthesiologists worked in urban hospitals. Urban facilities had higher median infrastructure and procedure scores compared with rural. Fifty-three individuals completed short-answer questions. Training was most desired in laparoscopic surgery and trauma management; less than half of establishments reported staff with trauma training. Conclusions: Surgical and trauma capacity in Potosí was most limited in personnel, infrastructure, and procedures at rural facilities, with greater personnel deficiencies than previously reported. Interventions should focus on increasing the number of surgical and anesthesia personnel in rural areas, with a particular focus on the reported desire for trauma management training. Results have been made available to key stakeholders in Potosí to inform targeted quality improvement interventions.